Exploring Human-Centered Design Strategies Towards Inclusive and Resilient Fishermen’s Housing in Coastal Settlements - Senasaputro, Bonifacio Bayu (RUAS, 2025)
Fishing communities in coastal areas face significant social, ecological, and food vulnerabilities due to climate change, tidal flooding (rob), and economic dependence on marine resources. These conditions create pressing challenges for housing and settlement planning, highlighting the need for adaptive, inclusive, and resilient design strategies. This study applies a Human-Centered Design (HCD) approach to explore solutions for inclusive and resilient fishermen’s housing. The methodology follows three key stages: (a) inspiration; gathering insights on community needs, behaviors, and cultural practices through participatory observation and in-depth interviews; (b) ideation; developing design concepts responsive to local lifestyles, spatial patterns, rapid construction and availability of material resources; and (c) implementation; prototyping and evaluating design solutions through user feedback. Findings reveal that integrating spatial flexibility, adaptive use of local materials, and features supporting self-sufficient food practices, such as hydroponic spaces and small-scale seafood processing areas, could significantly enhance both social and ecological resilience. The study further demonstrates that a Human-Centered Design framework enables communities to actively manage living environments, optimize daily routines, and strengthen economic and food autonomy. These insights provide actionable guidance for developing inclusive, resilient, and sustainable coastal housing, contributing to a broader understanding of resilient architecture in vulnerable human settlements.